Decentralization as a Post‐Conflict Stabilization Tool: The Case of Sierra Leone. (December 2016) - Edwards, Benjamin; Yilmaz, Serdar
Summary: Sierra Leone's experience with decentralization as a post‐conflict stabilization tool highlights both the value of making and keeping a promise to empower citizens through local government and the importance of fully implementing that promise over a longer time horizon. The emergence of the country from civil conflict into peace and stability is one of the greatest success stories of post‐conflict stabilization. Although the nation has enjoyed over a decade of peace (and peaceful transitions from party to party), many of the conditions that laid the groundwork for conflict remain, especially in rural areas, due to the partial implementation of the decentralization framework. Based on a post‐conflict perspective, we review the re‐emergence of local governments in Sierra Leone following the civil war, the institutional and legal framework within which they exist, and some of the remaining challenges the nation faces. Copyright © 2016 John Wiley & Sons, Ltd.